Assessment of Industry 4.0 Maturity in Procurement: An Application and Case Study - Parviainen, Henrik (My University, 2023)
Industry 4.0 has extended its scope out of the realms of manufacturing and begun to shape other areas of business, including procurement. As the industry, 4.0 technologies such as AI and blockchains continue to disrupt traditional ways of work across sectors. The vital question for procurement experts persists: what are the changes brought by industry 4.0 for the procurement domain, and how to address the readiness for these changes? This study connects the industry 4.0 phenomenon to procurement and supply chain management research by assessing industry 4.0 maturity in a case organization's procurement department. Industry 4.0 research has its roots in the manufacturing domain, but lately, research connecting the phenomenon to other business areas has gained ground in the academic literature. However, research linking industry 4.0 and procurement is still very nascent. This study attempts to empirically evaluate industry 4.0 maturity in procurement through an industry 4.0 maturity model by Schiele and Torn (2020). As this study builds a bridge between industry 4.0 and procurement, the theoretical framework presents a grid linking procurement value drivers to industry 4.0 technologies. The main findings in this research are twofold: the industry 4.0 maturity and development areas. Firstly, the identified industry 4.0 maturity level presents a holistic picture of the procurement department's current capabilities and readiness in the industry 4.0 domain. Secondly, the development areas recognized during the evaluation process offer managerial implications on how to improve the procurement function's industry 4.0 maturity. The research approach in this study followed a case study method, which offered the flexibility needed to measure the relatively novel phenomenon of industry 4.0 in a real-life setting. The data collection followed the notion of triangulation and was primarily based on the industry 4.0 maturity model by Schiele and Torn (2020).

Teollisuus 4.0-ilmiö koskettaa nykyään lähes kaikkia liiketoiminnan osa-alueita, mukaan lukien hankintatoimea. Teollisuus 4.0 teknologioiden, kuten tekoälyn ja lohkoketjujen jatkaessa perinteisten työskentelytapojen muuttamista, on hankintatoimen asiantuntijoilla esittää olennainen kysymys: mitkä ovat teollisuus 4.0:n vaikutukset hankintatoimeen ja kuinka valmistautua odotettavissa oleviin muutoksiin? Tässä tutkimuksessa yhdistetään teollisuus 4.0-ilmiö hankinnan ja toimitusketjun hallinnan tutkimukseen arvioimalla teollisuus 4.0-maturiteettia erään tapausorganisaation hankintaosastolla. Teollisuus 4.0 -tutkimuksen juuret ovat teollisuudessa, mutta viime aikoina akateemisessa kirjallisuudessa on yleistynyt tutkimus, joka yhdistää ilmiön muihin liiketoiminta-alueisiin. Teollisuus 4.0:n ja hankintatoimen yhdistävä tutkimus on kuitenkin vielä hyvin alkutekijöissään. Tämä tutkimus pyrkii empiirisesti arvioimaan teollisuus 4.0-maturiteettia hankintatoimessa Schielen ja Tornin (2020) teollisuus 4.0-maturitettimallin avulla. Koska tämä tutkimus rakentaa siltaa teollisuus 4.0:n ja hankintojen johtamisen välille, teoreettisessa viitekehyksessä esitetään ruudukko, joka yhdistää hankintatoimen arvoajurit ja teollisuus 4.0:n teknologioihin. Tämän tutkimuksen tärkeimmät havainnot ovat kaksitahoiset, ne ovat: teollisuus 4.0:n maturiteetti- ja tunnistetut kehitysalueet. Tunnistettu teollisuus 4.0:n maturiteettitaso antaa kokonaisvaltaisen kuvan tapausorganisaation hankintaosaston nykyisistä kyvyistä ja valmiuksista teollisuus 4.0:n kontekstissa. Arviointiprosessin aikana tunnistetut kehitysalueet puolestaan tarjoavat johtopäätöksiä siitä, miten hankintatoimen teollisuus 4.0 -maturiteettia voidaan kehittää. Tässä tutkimuksessa käytettiin tapaustutkimusmenetelmää, joka tarjosi tarvittavaa joustavuutta suhteellisen uuden teollisuus 4.0-ilmiön mittaamiseen todellisessa ympäristössä. Tiedonkeruussa pyrittiin noudattamaan triangulaation käsitettä, ja se perustui ensisijaisesti Schielen ja Tornin (2020) teollisuus 4.0-maturiteettimalliin.
Keywords: Industry 4.0, Procurement, Digitalization, AI, Big data analytics, automation, Teollisuus 4.0, hankintatoimi, digitalisaatio, tekoäly, big data analytiikka, automaatio